Association between Iron and Folic Acid Supplementation Adherence and Anemia among Adolescent Girls in Kulon Progo, Indonesia - Ramadhani, Khairunisa; Penak, Rahmatia Fitri; Muthi’ah, Tis’a Salma; Ayuningtyas, Cita Eri (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Introduction: Iron deficiency anemia remains a major public health concern among adolescent girls, particularly in low- and middle-income countries. Although iron and folic acid supplementation (IFAS) programs have been widely implemented in Indonesia, anemia prevalence remains high, suggesting potential challenges in adherence. Objective: This study aimed to examine the association between IFAS adherence and anemia among adolescent girls in Kulon Progo, Indonesia. Methods: A cross-sectional study was conducted between November 2024 and February 2025 among 71 female students aged 15–18 years selected through proportional random sampling. IFAS adherence was assessed using a structured questionnaire and categorized as adherent (≥4 tablets/month) or non-adherent (<4 tablets/month) based on national guidelines. Hemoglobin levels were measured using the Easy Touch GCHb device, and anemia was defined as hemoglobin <12 g/dL. Data were analyzed using the Chi-square test, with statistical significance set at p < 0.05. Results: The majority of participants were classified as non-adherent to IFAS (93.0%). Overall, 56.3% of respondents were anemic. A statistically significant association was observed between IFAS adherence and anemia status (p = 0.008). Non-adherent participants exhibited a substantially higher proportion of anemia compared with adherent participants Conclusion: Low adherence to iron supplementation was significantly associated with anemia among adolescent girls. Strengthening adherence-focused interventions, including nutrition education and school-based support strategies, is essential to enhance the effectiveness of anemia prevention programs in this population.